Analysis of Fashion Designing Area Common Vocabulary - Nunes, Luana Lamberti (BELT - Brazilian English Language Teaching Journal, 2014)
<!--[if gte mso 9]> <![endif]--> The goal of the article is to analyze the fashion designing area common vocabulary. The hypothesis is that the specific corpus which was used contains a great number of relevant terms that can be used to draw up a task for fashion designing students. The fashion designing corpus selected is composed of 10.213 words. The research has been carried out in three. The theoretical background used was composed by Corpus Linguistics and Terminology. The preceding results point out the relevance of the corpus for the specialized area researched. The relevance of the corpus in the specialized language researched was perceived in comparison with the common vocabulary of the general language. <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-fareast-language:EN-US;} --> <!--[endif] -->